The mediating role of healthy behaviors and self-perceived health in the relationship between eating behaviors and comorbidity in adults - Cristian Ramos-Vera; Gleni Quispe-Callo; Miguel Basauri-Delgado; Yaquelin E. Calizaya-Milla; Christian Casas-Gálvez; Norma Del Carmen Gálvez-Díaz; Jacksaint Saintila (BMC, 2024)
Abstract Background There is limited information on how healthy behaviors and individual health perceptions mediate the relationship between eating behaviors and noncommunicable diseases in adults. This study aimed to evaluate the mediating role of these factors in the relationship between eating behaviors and comorbidity in U.S. adults. Methods A cross-sectional predictive study using data from 5,247 adults from the Health Information National Trends Survey (HINTS) 5, cycle 3 (2019) was conducted. Structural equation modeling (SEM) was used to assess the mediating effect. Results The model showed good fit (χ2/df = 1.22, CFI = 971, TLI = 959, RMSEA = 0.050, SRMR = 0.036). It was found that self-perceived health totally mediated the relationship between eating behaviors and comorbidities (β = − 0.026, p < .001). Additionally, healthy behaviors and self-perceived health together mediated the relationship between eating behaviors and comorbidities (β = − 0.025, p < .001). A direct relationship was also observed between healthy behaviors and comorbidities, mediated by self-perceived health (β = − 0.103, p < .001). Conclusion The study concludes that eating behaviors are significantly related to comorbidities through the mediation of healthy behaviors and self-perceived health.